N-39=14-4n

Simple and best practice solution for N-39=14-4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for N-39=14-4n equation:


Simplifying
N + -39 = 14 + -4n

Reorder the terms:
-39 + N = 14 + -4n

Solving
-39 + N = 14 + -4n

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '39' to each side of the equation.
-39 + 39 + N = 14 + 39 + -4n

Combine like terms: -39 + 39 = 0
0 + N = 14 + 39 + -4n
N = 14 + 39 + -4n

Combine like terms: 14 + 39 = 53
N = 53 + -4n

Simplifying
N = 53 + -4n

See similar equations:

| y=14x+8b | | (2*17.50)+x=78 | | N-3n=14-2n | | y=14x+8x | | 4x+5/-3=7 | | 7x+12=5x-8 | | 0.5x+5=13 | | r^2-8r=-14 | | 3x-2=124 | | 7.1/44.2 | | 44.20/7.1 | | -7=11+v/5 | | x^5/7x | | 5t-20=-16+4t | | 20X^2-500=0 | | r^5/7r | | -5-23=7b+1 | | x+(-2)=-5 | | 7.3+9.4a+5.8-2.2a= | | 9r-19=-43+5r | | x/4.2=9.8 | | -3(4v-3)=81 | | 16-16k=20-2k | | 8+6a=-2a | | -51=3x-6(-x+25) | | 15=5/3m | | 4x+33+x+37=180 | | 9(x)=15 | | 7(3x+9)/2=6(2x+31)/4 | | 5x-10y=-5 | | -6(x+7)=-90 | | 17-4*n=11+2*n |

Equations solver categories